A precise calculation of power system frequency. - Jun-Zhe Yang
A precise digital algorithm based on discrete Fourier transforms (DFT) to estimate the frequency of a sinusoid with harmonics in real-time is proposed. This algorithm, that the authors call smart discrete Fourier transforms (SDFT), smartly avoids the errors that arise when frequency deviates from the nominal frequency, and keeps all the advantages of the DFT e.g., immunity to harmonics and the recursive computing can be used in SDFT. These make the SDFT more accurate than conventional DFT based techniques. In addition, this method is recursive and very easy to implement, so it is very suitable for use in real-time. The authors provide the simulation results compared with a conventional DFT method and second-order Prony method to validate the claimed benefits of SDFT
Keywords: Computer simulation; Digital algorithm; Frequency estimation; Harmonics immunity; Power system frequency calculation; Recursive computing; Smart discrete Fourier transform